Study on decorative art of greenbelt pastel Lotus Embossed Wuzi Dengke Bottle in Qing Dynasty / Li Ying and Wan Jamarul Imran Wan Abdullah Thani - -, Liying; Wan Abdullah Thani, Wan Jamarul Imran (Faculty of Art and Design, 2023)
China is a country with a long history of producing ceramics, leaving many exquisite and precious ceramic artworks. The ceramic involved in this paper is one of them. From the perspective of iconology, this study studies the Qing Dynasty porcelain “Greenbelt Pastel Lotus Embossed Wuzi Dengke Bottle” (GPLEWDB) through specific image analysis, including the form characteristics and symbolic meaning, historical background, and other contents of ceramic decoration. Then, according to the historical data, analyze the formation of the ceramic decorative art of social and cultural factors. This study attempts to change the traditional research methods of Chinese art history, in the form of case analysis, ceramic decorative elements of multi-level image analysis, to achieve a more in-depth study of ceramic cases. The study on the form and symbol of decorative patterns of GPLEWDB is helpful to link ceramic art research with ancient Chinese traditional culture, analyze the relationship between them, expand the perspective of traditional research, and promote the application of interdisciplinary research in ceramic research.